2013
DOI: 10.1007/s10441-013-9190-8
|View full text |Cite
|
Sign up to set email alerts
|

MitomiRs, ChloromiRs and Modelling of the microRNA Inhibition

Abstract: MicroRNAs are non-coding parts of nuclear and mitochondrial genomes, preventing the weakest part of the genetic regulatory networks from being expressed and preventing the appearance of a too many attractors in these networks. They have also a great influence on the chromatin clock, which ensures the updating of the genetic regulatory networks. The post-transcriptional inhibitory activity by the microRNAs, which is partly unspecific, is due firstly to their possibly direct negative action during translation by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…4B) and matches the corresponding AL sequence with 4 mutations in practically all D-loops of the mitochondrial DNA of individuals human from 164 countries and ethnic groups, and great apes 51 . The icosamer anti-matches (in red) like a microRNA, a sequence of the mitochondrial translocase precursor ENSG00000154174 52 , an enzyme crucial for the cell energetics in human cells: GGTGTGAAGTGGCATCTCATGGTGGTTTTGGTTTGCATTTCCCTAATG Translocase CCATGACATGTTATA AGTACCACAGACCGTCATTACATGCTTTATGT D-loop, giving an argument in favor of the ancient role of AL as a negative feedback regulator in the early energetic cell metabolism 30,53,54 -the CRISPR-CAS system provides bacteria like Rhodobacter sphaeroides with adaptive immunity and we can notice that the AL-pentamers ATGGT and ATTCA, and hexamers TCAAGAT and AATGGT (corresponding respectively to the Tψ− and D-loops of many tRNAs) are often observed at many levels of this system (CAS proteins, Casposon TIR and CRISP repeats). For example, the typical repeat sequences for CRISPR1 and CRISPR3 55 contain AL-heptamers from tRNA loops: GTTTTTGTACTCTCAAGATTTAAGTAACTGTACAAC (CRISPR1) GTTTTAGAGCTGTGTTGTTTCGAATGGTTCCAAAAC (CRISPR3) as well as the sequences of TIR and CRISPR compared in 56 , a consensus sequence from central part of the murine RSS VκL8, Jß2.6 and Jß2.2 [57][58][59] , and the human RSS spacer common for Vh, V328h2 and V328 60-62 : The probability p=2 10 -9 for 19 matches (with an insertion) between TIR and CRISPR using the binomial distribution B(1/4,22), p=8 10 -6 for 15 anti-matches between AL and CRISPR plus 1 quasi-anti-match G-T using the distribution B(1/4,21)xB(3/8,1), p=7 10 -4 for 13 matches between AL and consensus RSS using the binomial distribution B(1/4,22), p=2 10 -6 for 11 matches between AL and RSS spacer using the binomial distribution B(1/4,12)…”
Section: Discussionmentioning
confidence: 99%
“…4B) and matches the corresponding AL sequence with 4 mutations in practically all D-loops of the mitochondrial DNA of individuals human from 164 countries and ethnic groups, and great apes 51 . The icosamer anti-matches (in red) like a microRNA, a sequence of the mitochondrial translocase precursor ENSG00000154174 52 , an enzyme crucial for the cell energetics in human cells: GGTGTGAAGTGGCATCTCATGGTGGTTTTGGTTTGCATTTCCCTAATG Translocase CCATGACATGTTATA AGTACCACAGACCGTCATTACATGCTTTATGT D-loop, giving an argument in favor of the ancient role of AL as a negative feedback regulator in the early energetic cell metabolism 30,53,54 -the CRISPR-CAS system provides bacteria like Rhodobacter sphaeroides with adaptive immunity and we can notice that the AL-pentamers ATGGT and ATTCA, and hexamers TCAAGAT and AATGGT (corresponding respectively to the Tψ− and D-loops of many tRNAs) are often observed at many levels of this system (CAS proteins, Casposon TIR and CRISP repeats). For example, the typical repeat sequences for CRISPR1 and CRISPR3 55 contain AL-heptamers from tRNA loops: GTTTTTGTACTCTCAAGATTTAAGTAACTGTACAAC (CRISPR1) GTTTTAGAGCTGTGTTGTTTCGAATGGTTCCAAAAC (CRISPR3) as well as the sequences of TIR and CRISPR compared in 56 , a consensus sequence from central part of the murine RSS VκL8, Jß2.6 and Jß2.2 [57][58][59] , and the human RSS spacer common for Vh, V328h2 and V328 60-62 : The probability p=2 10 -9 for 19 matches (with an insertion) between TIR and CRISPR using the binomial distribution B(1/4,22), p=8 10 -6 for 15 anti-matches between AL and CRISPR plus 1 quasi-anti-match G-T using the distribution B(1/4,21)xB(3/8,1), p=7 10 -4 for 13 matches between AL and consensus RSS using the binomial distribution B(1/4,22), p=2 10 -6 for 11 matches between AL and RSS spacer using the binomial distribution B(1/4,12)…”
Section: Discussionmentioning
confidence: 99%
“…The 25 selected rings satisfy two opposite constraints corresponding to a min-max problem: (i) to be as short as possible, and (ii) to contain one and only one triplet corresponding to each amino acid synonymy class. The latter constraint would allow the rings to serve as a “matrimonial agency” concentrating amino acids in the vicinity of the ring and thereby favoring the links between any pair of them via peptide bonds [48,49,50,51,52,53,54,55]. The 25 RNA rings selected can be considered as ancestors of the tRNA of the 22 AAs including Pyrrolysine and Selenocysteine (Figure 3), with Serine counted twice, and Tyrosine and Aspartic Acid able to replace C by U in their tRNA anticodons [56,57].…”
Section: Construction Of the Al Rna Ringmentioning
confidence: 99%
“…Therefore, mitochondrial ncRNAs may participate in the fine-tuning of the mitochondrial energy supply. A recent study identified 13 miRNAs significantly enriched in mitochondria of HeLa cells, which actively participate in cell cycle and apoptosis through regulation of mitochondrial activity (Bandiera et al, 2011 ; Demongeot et al, 2013 ). The lncRNAs encoded by mtDNA, ASncmtRNA-1/2, are down-regulated in cancer cells and take part in the mitochondrial reprograming of oncogenic pathways (Burzio et al, 2009 ).…”
Section: Mitochondrial Metabolism In Cancer and Its Relation With Ncrmentioning
confidence: 99%